Project Xenos - Lim, Rachel Jeh Hwee (Nanyang Technological University, 2023)
An experimental typography project that utilizes artificial intelligence as a tool in typography design. ‘Project Xenos’ explores the symbiotic relationship between humans and machines throughout the creative design process.